Challenges and support needs in psychological and physical health among pilots: a qualitative study - Xu, Wen; Bao, Yuyan; Zhang, Lin; Li, Yunfei; Zhang, Erliang; Li, Huilun; Jin, Qingqing; Chen, Yan; Duan, Qingqing; Shi, Feng; Wang, Linlin; Lu, Ziyang; et al. (Frontiers in Public Health, 2024)
Introduction Physical and mental health problems among pilots affect their working state and impact flight safety. Although pilots’ physical and mental health problems have become increasingly prominent, their health has not been taken seriously. This study aimed to clarify challenges and support needs related to psychological and physical health among pilots to inform development of a more scientific and comprehensive physical and mental health system for civil aviation pilots. Methods This qualitative study recruited pilots from nine civil aviation companies. Focus group interviews via an online conference platform were conducted in August 2022. Colaizzi analysis was used to derive themes from the data and explore pilots’ experiences, challenges, and support needs. Results The main sub-themes capturing pilots’ psychological and physical health challenges were: (1) imbalance between family life and work; (2) pressure from assessment and physical examination eligibility requirements; (3) pressure from worries about being infected with COVID-19; (4) nutrition deficiency during working hours; (5) changes in eating habits because of the COVID-19 pandemic; (6) sleep deprivation; (7) occupational diseases; (8) lack of support from the company in coping with stress; (9) pilots’ yearly examination standards; (10) support with sports equipment; (11) respecting planned rest time; and (12) isolation periods. Discussion The interviewed pilots experienced major psychological pressure from various sources, and their physical health condition was concerning. We offer several suggestions that could be addressed to improve pilots’ physical and mental health. However, more research is needed to compare standard health measures for pilots around the world in order to improve their physical and mental health and contribute to overall aviation safety.